2009
DOI: 10.1183/09031936.00154409
|View full text |Cite
|
Sign up to set email alerts
|

Different definitions in childhood asthma: how dependable is the dependent variable?

Abstract: There is abundant literature on how to select and statistically deal with predictors in prediction models. Less attention has been paid to the choice of the outcome. We assessed the impact of different asthma definitions on prevalence estimates and on the prediction model's performances.We searched PubMed and extracted data of definitions used to diagnose childhood asthma (between 6 and 18 yrs) in cohort studies. Next, using data from an ongoing cohort study (n5186), we constructed and compared four prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 24 publications
1
70
0
Order By: Relevance
“…One of the challenges to understanding the pathophysiology and aetiology of this disease is the lack of consensus in defining asthma in the medical literature. A recent systematic review showed that in 122 publications investigating risk factors associated with childhood asthma, 60 different definitions were used [2]. Although many of these definitions were similar (with apparently subtle differences between them), the impact of this heterogeneity on the reported results and our understanding of asthma is unclear.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…One of the challenges to understanding the pathophysiology and aetiology of this disease is the lack of consensus in defining asthma in the medical literature. A recent systematic review showed that in 122 publications investigating risk factors associated with childhood asthma, 60 different definitions were used [2]. Although many of these definitions were similar (with apparently subtle differences between them), the impact of this heterogeneity on the reported results and our understanding of asthma is unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Although many of these definitions were similar (with apparently subtle differences between them), the impact of this heterogeneity on the reported results and our understanding of asthma is unclear. When four of the most commonly used definitions were applied to a high risk population of 186 children, the overall agreement was 61%, indicating that 39% of the children could move from 'asthma' to 'not asthma' depending on which definition was used [2]. Such variability will obviously affect the performance of prediction models.…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, in studies about asthma in children, several definitions of asthma and wheezing phenotypes are used [23]. To accomplish a large sample of newborns and a high participation rate, it was decided not to perform invasive tests in the WHISTLER project.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 30 major studies on the association published worldwide, nearly a third reported null effects, whereas the others reported significant associations, with odds ratios ranging from 1.2 to 4.9 (4). We suspected that inconsistencies in the PTB-asthma association in part reflected differences among studies in three key domains: definitions of asthma (6), degree of prematurity, and the age when asthma was assessed.…”
mentioning
confidence: 92%